Assessor pedagógico: perspectivas e desafios no assessoramento pedagógico nas escolas indígenas e nos centros municipais de educação escolar indígena de Manaus - Ribeiro, Giovana de Oliveira (2020)
The research addresss the practice of advising teachers of Indigenous School Education in Manaus, which is carried out by pedagogical advisers. Despite the relevant role that these advisors play, their performance is permeated by some gaps, among them the lack of clarity of a professional profile and the lack of training to exercise this function, which leads to high turnover in the occupation of this position. The present study has the general objective of detecting the main challenges and perspectives of pedagogical advisers working in the indigenous municipal education of Manaus. The methodological procedures adopted for this research included bibliographic research on indigenous educational issues combined with semi structured interviews with 7 members (among indigenous advisers and teachers) who directly experience the peculiarities of teaching aimed at the indigenous population. The results point out that among the challenges faced by these professionals, the difficulties of locomotion to acess th advisory places are highlighted, lack of adequate preparation for the exercise of the function and inexistence of program focused on the planning of the advisory activities. The educational product resulting from this master’s research proposes a set of actions that, when put into practice, make work of pedagogical advisors more assertive. The material in anchored in 4 areas of action: Pedagogical; Political-Pedagogical; Production of Didactic Material and Linguistic. The product was presented and validated with its target audience and the expectation is that from the adoption of existing practices in its contente, the advice provided to indigenous teachers will be carried out in a more organized and planner manner, with a focus on improving quality of education offered to the indigenous population of the city of Manaus.